Dinâmica reprodutiva, estrutura populacional e ecologia trófica de Prochilodus lineatus (Valenciennes, 1836) em três áreas de influência de uma grande barragem hidrelétrica neotropical - Santos, Adriani Cristina Monteiro dos (2021)
The hydroelectric projects promote several changes in the reproduction, migration and natural feeding of migratory fish, which can result in population differences between downstream and upstream of the dam. Although fish ladders are built to minimize the effects of the dam on fish migration, many questions about the population behavior of migratory fish in the use of the fish ladder have not yet been addressed. This study aimed to analyze the reproductive dynamics, population structure and trophic ecology of P. lineatus in the downstream environment, fish ladder and upstream (reservoir) of the Porto Primavera HPP. We sampled specimens in these three sections, evaluating the spatial differences in reproductive rates, sex ratio, size and growth, age structure, dietary rates and diet composition. The results show that P. lineatus reproduces upstream and downstream of the dam. However, hydroelectric operations affect reproductive synchronization with environmental stimuli. Spatial differences in sex ratio, size, growth and age composition were recorded. There were differences in feeding activity between the three environments, and the species' diet was different between downstream and ladder for fish, since this system may have been restricting or promoting the abundance of some food resources.